Maiya Hannon: capstone - Hannon, Maiya, artist (Colorado State University. Libraries, 2021)
The artist's statement: Trauma is defined as a "deeply distressing or disturbing experience". I gather inspiration from the trauma that resides within. Flashes of pain and intense emotion cloud my mind as I attempt to navigate throughout my daily life. Through my artistic practice I face the entity within with grace and confidence. I see it for what it is: the result of an experience. This experience is impactful, yet it does not define me. I reclaim my mind and body through abstract self representation within my work. I use my own face and body as inspiration and as a tool, which forces me to essentially face my demons as well as reality head on. My work is also driven by an element of process. I demonstrate various processes through anatomical monoprinting, chemically altering materials, hammering metals, and integrating metallic elements in contrast with clear or opaque surfaces. While these techniques can be tedious, they are not perfect, placing emphasis on the element of chance. Each print, twist, and chemical reaction is extremely unpredictable which prevents me from knowing exactly what a finished piece will look like. This evokes a process within myself: the process of letting go. This is crucial to my personal healing process, and I demonstrate this vulnerability through creation. By leaving aspects of my work to chance I surrender to the piece, allowing and accepting any and all "mistakes" that occur. Previously, I have struggled with the idea of how to address my trauma and healing process through my practice, however, I feel that I am in a position to do that now. My work not only serves as a visual representation of my experience, but also a representation of how trauma can affect people in general, even to the point of deterioration. Leaving only an imprint of themselves behind.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing